Anne W. Marks papers - Marks, Anne W., 1922-2006.
Chiefly letters to Marks from Felix Frankfurter relating to national and international events and to personal matters. Other correspondents include Hubert H. Humphrey, Herbert S. Marks, and J. Robert Oppenheimer. Subjects include Oppenheimer, his receipt of the Enrico Fermi Award for contributions to theoretical physics, and revocation of his security clearance; the John F. Kennedy presidential inauguration; Bay of Pigs invasion of Cuba, 1961; and Anne W. Marks's work for the U.S. Arms Control and Disarmament Agency in Geneva, Switzerland. Includes photographs of Frankfurter.
Secretary to physicist J. Robert Oppenheimer during World War II and arms control activist.
Collection material in English.
Keywords: Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Kennedy, John F. -- 1917-1963 -- Inauguration, 1961.; Marks, Herbert S., -- 1907-1960 -- Correspondence; Oppenheimer, J. Robert, -- 1904-1967.; Oppenheimer, J. Robert, -- 1904-1967 -- Correspondence; United States. -- Arms Control and Disarmament Agency; Arms control; Atomic bomb; Disarmament; History, Modern -- 20th century; Internal security -- United States; International relations; Physics -- Awards; Cuba -- History -- Invasion, 1961.; United States -- Foreign relations -- 1945-1989.; United States -- Politics and government -- 1945-1989; Arms control activists; Secretaries